Growth, profits and R&D investment. Issue 1 (1st January 2018) - Lee, Sanghoon
Abstract : This study uses firm-level panel data from Korea over the period 1990–2012 to examine the relationship between growth, profitability and R&D investment. The empirical results show that (i) the effect of profits on growth is negative, which, however, isy significant only after the financial crisis; (ii) the effect of growth on profits is insignificant, but a positive relationship is found before the crisis and for old firms; and (iii) there is an inverse U-shaped relationship between R&D investment and cash flow, and the effect of cash flow on R&D investment is positive before the crisis and for non-group firms. The empirical results reflect the institutional setting and historical context of Korea. Theoretical and practical implications are discussed.